Factors influencing kidney transplantation rates: a study from the ERA Registry - Boenink, Rianne; Kramer, Anneke; Vanholder, Raymond C; Mahillo, Beatriz; Massy, Ziad A; Bušić, Mirela; Ortiz, Alberto; Stel, Vianda S; Jager, Kitty J; null, null; Barbullushi, M; Idrizi, A; et al. (Oxford University Press (OUP), 2023)
Background Large international differences exist in kidney transplantation (KT) rates. We aimed to investigate which factors may explain the total, deceased donor and living donor KT rates over the last decade. Methods KT experts from 39 European countries completed the Kidney Transplantation Rate Survey on measures and barriers and their potential effect on the KT rate in their country. In the analyses, countries were divided into low, middle and high KT rate countries based on the KT rate at the start of study period in 2010. Results Experts from low KT rate countries reported more frequently that they had taken measures regarding staff, equipment and facilities to increase the total KT rate compared with middle and high KT rate countries. For donor type–specific KT, the largest international differences in measures taken were reported for deceased donor KT, with middle and high KT rate countries taking more measures, such as the use of expanded criteria donor kidneys, the presence of transplantation coordinators and (inter)national exchange of donor kidneys. Once a measure was taken, experts’ opinion on its success was similar across the low, middle and high KT rate countries. Experts from low KT rate countries more often reported potential barriers, such as patients’ lack of knowledge and distrust in the healthcare system. Conclusions Particularly in low KT rate countries, the KT rate might be stimulated by optimizing staff, equipment and facilities. In addition, all countries may benefit from measures specific to deceased and living donors.